INVESTIGATING STUDENTS’ ABILITY ON LEARNING TENSES BY APPLYING ONLINE LEARNING DURING COVID-19 PANDEMIC - Merlin Helentina Napitupulu (Jurnal Scientia, 2021)
This research aimed to know students’ ability on learning tenses by applying online learning at Timor University during Covid-19 Pandemic. This research focused on the student’s ability on learning tenses: simple present tense and past tense. This research was categorized as descriptive qualitative research method. The population of the research was the second semester students majoring government sciences at Timor University which consists of four classes. The sample of the research was taken by clustering sampling and the students of Class D were chosen as the sample in this research. This research used test to know the students’ ability on learning tenses and also used interview as the instruments of data collection. The finding of this research showed that the students’ ability on learning simple present tense was fair. It was shown by the average score in the form of the simple present tense is 64, meanwhile the students’ ability on learning simple past tense was good, it was shown by the average score in the form of the simple past tense is75. The students got many difficulties on learning simple present tense. In conclusion, the result of the test showed that the students’ ability in using simple present tense was on fair level. From the data got it showed that the average score on learning tenses: simple present tense and past tense was 69.